2021
DOI: 10.1101/2021.10.28.466308
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent evolutionary trajectories of bryophytes and tracheophytes from a complex common ancestor of land plants

Abstract: The origin of plants and their colonization of land resulted in the transformation of the terrestrial environment. Here we investigate the evolution of the land plants (embryophytes) and their two main lineages, the tracheophytes (vascular plants) and bryophytes (non-vascular plants). We used new fossil calibrations, relative lineage dating implied by horizontal gene transfer, and new phylogenomic methods for mapping gene family origins. Distinct rooting strategies resolve tracheophytes and bryophytes as monop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 197 publications
(187 reference statements)
0
8
0
Order By: Relevance
“…In bryophytes, that diverged from vascular plants ca. 500-460 MYA and comprise hornworts, liverworts and mosses 20 , a large fraction of TEs are covered by H3K27me3 in the liverwort Marchantia polymorpha 9 while TEs in the model moss Physcomitrium patens are covered mostly by H3K9me2 21 . To address the conservation of the association of H3K27me3 with TEs among bryophytes, we used the model hornwort Anthoceros agrestis that diverged from bryophyte ancestors before the divergence of liverworts from mosses 22 .…”
Section: Association Of H3k27me3 Marks On Tes Are Conserved Among Bry...mentioning
confidence: 99%
“…In bryophytes, that diverged from vascular plants ca. 500-460 MYA and comprise hornworts, liverworts and mosses 20 , a large fraction of TEs are covered by H3K27me3 in the liverwort Marchantia polymorpha 9 while TEs in the model moss Physcomitrium patens are covered mostly by H3K9me2 21 . To address the conservation of the association of H3K27me3 with TEs among bryophytes, we used the model hornwort Anthoceros agrestis that diverged from bryophyte ancestors before the divergence of liverworts from mosses 22 .…”
Section: Association Of H3k27me3 Marks On Tes Are Conserved Among Bry...mentioning
confidence: 99%
“…We found that the gene content of hornworts is significantly lower than tracheophytes and other bryophytes (ANOVA; F = 129.5; d.f. = 2,30; p < 0.001), thereby suggesting that hornwort diversification and speciation were accompanied by significant instances of gene loss ( Supplementary Figure 2 ), even more than what is observed for bryophytes in general ( Harris et al, 2021 ).…”
Section: Hornworts Underwent Significant Instances Of Gene Lossmentioning
confidence: 83%
“…It is evident that hornwort—and bryophyte—emergence and diversification were accompanied by major instances of gene loss ( Harris et al, 2021 ). Our results reinforce this hypothesis, specifically highlighting that the combined loss of certain genes may be responsible for the unique plastid phenotype observed in this group.…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that hornwort – and bryophyte – emergence and diversification was accompanied by major instances of gene loss (Harris et al 2021). We suggest that a consequence of some of plastid-related gene losses, namely the combined loss of FtsZ2 and ARC3, resulted in hornworts reverting back to a monoplastidic phenotype, which the embryophyte ancestor was able to escape.…”
Section: Discussionmentioning
confidence: 99%